Near-death experience in indigenous religions - Shushan, Gregory (Oxford University Press, 2018)
"In this book, Gregory Shushan explores the relationship between [near death experiences], shamanism, and beliefs about the afterlife in traditional indigenous societies in Africa, North America, and Oceania. Drawing on historical accounts of the earliest encounters with explorers, missionaries, and ethnologists, this study addresses questions such as: Do ideas about the afterlife commonly originate in NDEs? What role does culture play in how people experience and interpret NDEs? How can we account for cross-cultural similarities and differences between afterlife beliefs? Though NDEs are universal, Shushan shows that how they are actually experienced and interpreted varies by region and culture" (Book jacket)